A 2D software system for expedite analysis of CFD problems in complex geometries. Issue 1 (22nd June 2015) - Lopes, A. M. G.
ABSTRACT: EasyCFD_G, a 2D software tool for fluid dynamics and heat transfer applications, is presented. The underlying physical and numerical principles are described, including mesh generation. The software is based on quadrilateral structured and unstructured meshes, rendering it with great versatility in geometrical terms. Amenable problems include multi‐domain simulations with fluid and solid regions, thermal effects and mixing of different fluids, in stationary or turbulent regime. For illustration, a few example problems are presented, covering different physical situations, including comparison with benchmark data. Due to its versatility, fast learning curve and easy and intuitive utilization, this software tool represents a great value for educational purposes. © 2015 Wiley Periodicals, Inc. Comput. Appl. Eng. Educ. 24:27–38, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21668